2004
DOI: 10.1002/app.20338
|View full text |Cite
|
Sign up to set email alerts
|

Determination of monomer reactivity ratios in styrene/2‐ethylhexylacrylate copolymer

Abstract: ABSTRACT:The monomer reactivity ratios for styrene/ 2-ethylhexylacrylate in bulk at 80°C were investigated by studying the resulting copolymer composition via 1 H-NMR. Composition results were summarized and various methods were employed to estimate the reactivity ratios including the use of the Error-in-Variables-Model (EVM) approach by using the Mayo-Lewis model. The estimates of the reactivity ratios from the EVM method are found to be r s ϭ 0.979 and r EHA ϭ 0.292. The resulting copolymer has a tendency to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They reported the reactivity ratios for styrene and EHA as 0.10 and 0.175 respectively. Moreover, Kavousian et al reported the copolymerization of styrene and EHA via conventional radical polymerization (Kavousian et al, 2004 ). They reported the reactivity ratio of styrene and EHA as 0.926 and 0.238 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported the reactivity ratios for styrene and EHA as 0.10 and 0.175 respectively. Moreover, Kavousian et al reported the copolymerization of styrene and EHA via conventional radical polymerization (Kavousian et al, 2004 ). They reported the reactivity ratio of styrene and EHA as 0.926 and 0.238 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…So the copolymers of EHA are widely used in paints, coating and adhesive applications (Skeist, 1977 ; Plessis et al, 2001 ; Webster and Crain, 2002 ). Copolymerization is an important synthetic tool which can control the thermal and mechanical properties of the polymers (Kavousian et al, 2004 ). In the copolymers of styrene and EHA, the properties of the copolymers can be monitored by controlled incorporation of the respective comonomers styrene and EHA.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the commercial importance of HIPS, a lot of studies deal with synthesis, process modeling, and characterization of this polymer. 7 In 1986, Hobbs reported effects of rubber particle size on impact strength property of high impact polystyrene. 8 In 1990, Peng and coworkers studied the effects of grafting and cross-linking of polybutadiene during the bulk polymerization of high impact polystyrene.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of wide use of EHA, data on its relative activities in copolymerization with other monomers are limited in the literature; only data on the characteristics of conjugation effects and polar effects in the monomer are available [8,9]. Data on the thermodynamic properties of initial EHA and copolymers based on it are almost absent.…”
Section: Introductionmentioning
confidence: 97%